2021
DOI: 10.4103/idoj.idoj_257_20
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathological Study of Skin Tumors from a Tertiary Care Centre in North India

Abstract: Background: There is a huge spectrum of skin tumors which can be confused clinically with malignancies, particularly when they are pigmented or inflamed, and histopathological examination of a biopsy specimen is required to establish a definitive diagnosis and to facilitate appropriate intervention and follow up. Aim: To evaluate all skin tumors and categorize them according to their origin. Methods: The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…The peak incidence was in adult age group in the present study in concordance with the Patel N et al [13], Goel P et al [14] and Shrivastava V et al [15]. Male to female ratio was 1 :1.15 in the current study.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The peak incidence was in adult age group in the present study in concordance with the Patel N et al [13], Goel P et al [14] and Shrivastava V et al [15]. Male to female ratio was 1 :1.15 in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Our study reported a major involvement of extremities i.e. 43.08%, which wasn't consistent with the findings of Patel N et al [13], Goel P et al [14] and Shrivastava V et al [15] who majorly had head and neck involvement (Table 2).…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations